Molecular identification, virulence gene profiling, and antifungal susceptibility of Candida albicans isolates from women with urinary tract infections - Muna F. Jihad; Manal B. Salih (Український Журнал Нефрології та Діалізу)
Candida species are increasingly recognized as causative agents of urinary tract infections (UTIs), particularly in immunocompromised individuals. Among them, Candida albicans is the most prevalent and exhibits virulence factors that enhance adhesion, biofilm formation, and antifungal resistance. This study investigates the molecular identification, antifungal resistance profiles, and virulence gene prevalence (ALS1, ALS3, HWP1) in C. albicans isolates from women with UTIs in Thi-Qar Province, Iraq.